ANALYZING STUDENTS’ EXPERIENCE IN LMS SPOT UPI USING THE UEQ - Azhari, Fairuz Azka; Asep Nuryadin; Muhammad Dzikri Ar Ridlo (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: The rapid expansion of digital learning environments has increased students’ reliance on Learning Management Systems (LMS), including SPOT UPI. However, limited studies have examined the platform’s overall user experience across all User Experience Questionnaire (UEQ) dimensions. This study aims to evaluate the user experience (UX) of SPOT UPI, identify its strengths and weaknesses, and provide recommendations for system improvement. A quantitative-dominant mixed-method design was applied, involving 81 student respondents for the UEQ survey and two participants for follow-up semi-structured interviews selected through purposive sampling. The UEQ data were analyzed to generate mean scores for six UX dimensions, while interview data were thematically analyzed to support the interpretation of quantitative findings. The results indicate that Perspicuity (1.05) and Efficiency (0.78) achieved the highest scores, reflecting adequate clarity and functionality. In Contrast, Stimulation (0.50) and Novelty (-0.15) were the lowest, indicating limited engagement and innovation. Overall, pragmatic quality (0.84) outperformed hedonic quality (0.17), suggesting that users value functionality more than enjoyment. In conclusion, SPOT UPI is generally usable but lacks aesthetic appeal, emotional engagement, and innovative features, highlighting the need for interface redesign and performance optimization to enhance the overall learning experience. Keywords: learning management system; user experience; user experience questionnaire Abstrak: Perkembangan pembelajaran digital membuat mahasiswa semakin bergantung pada Learning Management System (LMS), termasuk SPOT UPI. Meski digunakan secara luas, evaluasi pengalaman pengguna secara komprehensif berdasarkan seluruh dimensi User Experience Questionnaire (UEQ) masih belum banyak dilakukan. Penelitian ini bertujuan untuk mengevaluasi user experience (UX) pada SPOT UPI, mengidentifikasi keunggulan dan kelemahannya, serta memberikan rekomendasi perbaikan sistem. Penelitian menggunakan desain penelitian mixed-method dominan kuantitatif, melibatkan 81 responden pada survei UEQ dan dua partisipan pada wawancara semi-terstruktur yang dipilih melalui purposive sampling. Data UEQ dianalisis untuk memperoleh nilai rata-rata pada enam dimensi UX, sedangkan data wawancara dianalisis secara tematik untuk memperkaya interpretasi temuan kuantitatif. Hasil menunjukkan bahwa Perspicuity (1,05) dan Efficiency (0,78) menjadi dimensi dengan skor tertinggi, mencerminkan bahwa SPOT UPI mudah dipahami dan cukup membantu dalam menyelesaikan tugas. Sebaliknya, Stimulation (0,50) dan Novelty (-0,15) memperoleh skor terendah, menandakan rendahnya tingkat keterlibatan dan inovasi yang dirasakan pengguna. Secara keseluruhan, pragmatic quality (0,84) lebih tinggi dibandingkan hedonic quality (0,17), menunjukkan bahwa pengguna lebih mengutamakan aspek fungsional daripada kenyamanan emosional. Temuan tersebut mengindikasikan bahwa SPOT UPI sudah layak digunakan secara fungsional, tetapi masih memerlukan peningkatan pada interface, pengalaman visual, dan fitur inovatif agar dapat memberikan pengalaman belajar digital yang lebih menarik dan optimal. Kata kunci: learning management system; pengalaman pengguna; user experience questionnaire